2004
DOI: 10.1111/j.1469-7610.2004.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Do risk factors for problem behaviour act in a cumulative manner? An examination of ethnic minority and majority children through an ecological perspective

Abstract: The support for the cumulative hypothesis highlights the importance of having a broad picture of children's characteristics and environmental components when analysing children's adjustment. The distinct influence of risk stemming from the different ecological levels suggests that the trajectories of internalising, externalising and total problem behaviour may be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
1
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(129 citation statements)
references
References 47 publications
11
104
1
8
Order By: Relevance
“…This is consistent with our previous results which indicated that externalizing problems were influenced mainly by factors at the level of the child's proximal environment (i.e., the microsystem level; Bronfenbrenner, 1979) such as parental positivity and parent-child dyadic mutuality, whereas internalizing problems were more strongly linked to the child's own attributes (e.g., self-worth, temperament) as well as more distal factors such as socioeconomic status (Atzaba-Poria et al, 2004).…”
Section: Mutuality and Child Behavior Problemssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with our previous results which indicated that externalizing problems were influenced mainly by factors at the level of the child's proximal environment (i.e., the microsystem level; Bronfenbrenner, 1979) such as parental positivity and parent-child dyadic mutuality, whereas internalizing problems were more strongly linked to the child's own attributes (e.g., self-worth, temperament) as well as more distal factors such as socioeconomic status (Atzaba-Poria et al, 2004).…”
Section: Mutuality and Child Behavior Problemssupporting
confidence: 92%
“…Therefore, we focused on externalizing problems in the current paper. However, there was a modest ethnic group difference in child internalizing problems that we describe in another paper (Atzaba-Poria, Pike, & Deater-Deckard, 2004). …”
Section: Acknowledgementsmentioning
confidence: 54%
“…Such a pathway of accumulation of multiple risks has been tested in several studies with community-sample or referred subjects, demonstrating a significant linear relation between the cumulative risk index, computed by summing the number of dichotomized risk factors such as high vs. low IQ, secure vs. insecure attachment, or good vs. poor parenting for example, and children's or adolescents' externalizing or internalizing behavior (Appleyard, Egeland, van Dulmen, & Sroufe, 2005;Atzaba-Poria, Pike, & Deater-Deckard, 2004;Gerard & Buehler, 2004;Greenberg et al, 2001;Lanza, Rhodes, Nix, & Greenberg, 2010;Lucio, Rapp-Paglicci, & Rowe, 2011;Roskam, Meunier, Stievenart, & Noël, 2013;Trentacosta et al, 2008). Some of these studies were cross-sectional like the present one, and therefore unable to address the core question of the directionality of the effects (e.g., Atzaba-Poria et al, 2004;Greenberg et al, 2001). Rather they contributed to documenting the association between multiple specific risks which are combined together and general issues.…”
Section: The Cumulative Effect Hypothesismentioning
confidence: 99%
“…A common feature of these studies is the use of combined indicators from the domains (community, school, family, and peers) into a single cross-domain composite factor. Although this methodology offers certain advantages [14], it obviates the ability to explore some central questions.First, there is ambiguity about the interrelations among risk and protective factors and, more precisely, the relations between different risk factors and specific adolescent outcomes [18,19]. Research indicates variation in the magnitude of relations and that generally, risk factors are more influential than protective factors [20,21].…”
mentioning
confidence: 99%